2012
DOI: 10.1007/s00125-012-2710-2
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 (MCP-1) deficiency enhances alternatively activated M2 macrophages and ameliorates insulin resistance and fatty liver in lipoatrophic diabetic A-ZIP transgenic mice

Abstract: Aims/hypothesis Monocyte chemoattractant protein-1 (MCP-1)/chemokine (C-C motif) ligand (CCL) 2 (CCL2) secreted from white adipose tissue (WAT) in obesity has been reported to contribute to tissue macrophage accumulation and insulin resistance by inducing a chronic inflammatory state. MCP-1 has been shown to be elevated in the fatty liver of lipoatrophic A-ZIP-transgenic (A-ZIP-Tg) mice. Treatment of these mice with the CC chemokine receptor (CCR) 2 antagonist has been shown to ameliorate the hyperglycaemia, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 38 publications
(60 reference statements)
3
50
1
1
Order By: Relevance
“…In this sense, the activation of JNK as a main mechanism for the development of steatohepatitis has been largely described (Schattenberg et al 2006, Tuncman et al 2006, Singh et al 2009. Others have shown a relevant role of p38-activation in fatty liver disease (Menghini et al 2012, Nio et al 2012, Song, et al 2014. In addition, NEFA liberated by HSL activate both p38 and JNK, and p38 mediates proinflammatory cytokine expression in adipose tissue (Mottillo, et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the activation of JNK as a main mechanism for the development of steatohepatitis has been largely described (Schattenberg et al 2006, Tuncman et al 2006, Singh et al 2009. Others have shown a relevant role of p38-activation in fatty liver disease (Menghini et al 2012, Nio et al 2012, Song, et al 2014. In addition, NEFA liberated by HSL activate both p38 and JNK, and p38 mediates proinflammatory cytokine expression in adipose tissue (Mottillo, et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time Quantitative RT-PCR-Real-time quantitative RT-PCR was performed by the method described previously (30,31). Total RNA was prepared from the epididymal WAT and liver using TRIzol (Invitrogen) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The TaqMan probes were used for mouse acyl-CoA oxidase 1 (ACOX1 encoded by Acox1), Mm01184029_m1; CD206 (Mrc1), Mm00485148_m1; CD36 (Cd36), Mm 01135198_m1; CD68 (Cd68), Mm00839636_g1; F4/80 (Emr1), Mm00802530_m1; fatty acid synthase (FAS, Fasn), Mm01253292_m1; IL-1␤ (Il1b), Mm00434228_m1; leptin (Lep), Mm 00434759_m1; lipoprotein lipase (LPL, Lpl), Mm00434764_m1; macrophage-1 antigen (Mac-1, Itgam), Mm00434455_m1; monocyte chemoattractant protein-1 (MCP-1, Ccl2), Mm 00441242_m1; phosphoenolpyruvate carboxykinase (PEPCK, Pck1), Mm 00447183_m1; peroxisome proliferator-activated receptor ␥ coactivator 1␣ (PGC1␣, Ppargc1a), Mm 01344232_g1; sterol regulatory element-binding protein-1c (SREBP-1c, Srebf1), Mm 00550338_m1; TNF-␣ (Tnf), Mm00443260_g1; Toll-like receptor 4 (TLR4, Tlr4), Mm 00494069_m1; uncoupling protein 1 (UCP1, Ucp1), Mm00445273_ m1; uncoupling protein 2 (UCP2, Ucp2), Mm00495907_g1; 36B4 (Rplp0), Mm00725448_s1. The primers and the probe for mouse cyclophilin A (Ppia) were as follows: the forward primer was 5Ј-ggtcctggcatcttgtccat-3Ј, the reverse primer was 5Ј-cagtcttggcagtgcagataaaa-3Ј, and the probe was 5Ј-ctggaccaaacacaaacggttccca-3Ј (31). The relative amount of each transcript was normalized to the amount of Rplp0 or Ppia transcripts as internal standards.…”
Section: Methodsmentioning
confidence: 99%
“…Knockout mouse studies have shown that CCR2 and its ligand CCL2 are pivotal in triggering obesity-induced insulin resistance and are required for accumulation of inflammatory macrophages in fat (67)(68)(69)(70). CCL2 was also shown to increase macrophage content via ATM proliferation, in addition to its effect on blood monocyte recruitment (71).…”
Section: Tgr5mentioning
confidence: 99%